Antifungal trichothecene sesquiterpenes obtained from the culture broth of marine-derived Trichoderma cf. brevicompactum and their structure-activity relationship. Issue 17 (1st September 2020) - Yamazaki, Hiroyuki; Yagi, Akiho; Takahashi, Ohgi; Yamaguchi, Yuga; Saito, Anri; Namikoshi, Michio; Uchida, Ryuji
Graphic abstract: Highlights: Two new trichothecene derivatives were isolated from the culture broth of Trichoderma cf. brevicompactum TPU199. The structures of the new trichothecenes were elucidated based on their 1D and 2D NMR spectra. The structure-activity relationship of anti-fungal trichothecenes was investigated. Abstract: Two new trichothecene sesquiterpenes, trichobreols D (1 ) and E (2 ), were isolated from the culture broth of marine-derived Trichoderma cf. brevicompactum together with trichobreol A (3 ). The structures of 1 and 2 were assigned on the basis of their spectroscopic data. Compound 1 inhibited the growth of two yeast-like fungi, Candida albicans and Cryptococcus neoformans, with equivalent MIC values (6.3 μg/mL), while 2 gave MIC values of 12.5 and 25 μg/mL, respectively. The antifungal activities of five semisynthetic derivatives (4 –8 ) prepared from 3 were evaluated and compared to investigate the preliminary structure-activity relationship.